If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + -18 * 4 = -36 Multiply -18 * 4 5t + -72 = -36 Reorder the terms: -72 + 5t = -36 Solving -72 + 5t = -36 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '72' to each side of the equation. -72 + 72 + 5t = -36 + 72 Combine like terms: -72 + 72 = 0 0 + 5t = -36 + 72 5t = -36 + 72 Combine like terms: -36 + 72 = 36 5t = 36 Divide each side by '5'. t = 7.2 Simplifying t = 7.2
| 7x+y+9=0 | | 812x+2469x=180 | | x+2=-10+7x | | f(4)=4-1 | | f(0)=0-1 | | f(-5)=-5-1 | | 2.5=(2)t+(.5)(-9.8)t^2 | | 2k-5x+6.3=14.4 | | 4=6-7a+5 | | 5x^4-2x^3+40x-16=0 | | f(5)=-4(5)-5 | | (-1/3)(-3/5) | | 6x+2/3=180 | | 3x+2(x-4)=7x | | (3/5)(15c+10)=12c-9 | | 400+4.50n= | | -8u+3=2u-17 | | 15/25 | | 2/16=x/100 | | f(0)=-4(0)-5 | | 5x-7=3(2x-4) | | x-7=2x+5-4x | | 7/2x-81=360 | | 5x-2+3x=4x-14 | | X/14=o | | 5(x+4)=28+3x | | M(m+10)+2m=180 | | x^3+14x=5 | | f(-4)=-4(-4)-5 | | -3+11= | | 3(4x-c)=3a+2c | | -17+10b=-9b+2b |